2022
DOI: 10.3390/molecules27051700
|View full text |Cite
|
Sign up to set email alerts
|

Optical Dynamic Nuclear Polarization of 13C Spins in Diamond at a Low Field with Multi-Tone Microwave Irradiation

Abstract: Majority of dynamic nuclear polarization (DNP) experiments have been requiring helium cryogenics and strong magnetic fields for a high degree of nuclear polarization. In this work, we instead demonstrate an optical hyperpolarization of naturally abundant 13C nuclei in a diamond crystal at a low magnetic field and the room temperature. It exploits continuous laser irradiation for polarizing electronic spins of nitrogen vacancy centers and microwave irradiation for transferring the electronic polarization to 13C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Here, T 1 was found to depend strongly on B 0 and different means to prolong T 1 were suggested (Ajoy et al, 2019). Most recently, it was found that using microwaves with three different wavelengths (matching the resonance frequency of the hyperfine interactions between the 15 N and the electron) improved the polarization, yielding to an increase of 13 C bulk polarization from 0.068% to 0.113% (Kavtanyuk et al, 2022). While the optical detection of NV centers is sensitive, the achieved polarization levels still remain significantly below what 1 H, 13 C, 15 N, or 129 Xe spin systems can provide for inductive detection.…”
Section: Nanomaterials In Hyperpolarization For Medical Imagingmentioning
confidence: 99%
“…Here, T 1 was found to depend strongly on B 0 and different means to prolong T 1 were suggested (Ajoy et al, 2019). Most recently, it was found that using microwaves with three different wavelengths (matching the resonance frequency of the hyperfine interactions between the 15 N and the electron) improved the polarization, yielding to an increase of 13 C bulk polarization from 0.068% to 0.113% (Kavtanyuk et al, 2022). While the optical detection of NV centers is sensitive, the achieved polarization levels still remain significantly below what 1 H, 13 C, 15 N, or 129 Xe spin systems can provide for inductive detection.…”
Section: Nanomaterials In Hyperpolarization For Medical Imagingmentioning
confidence: 99%